2004
DOI: 10.1159/000079664
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Transporter as a Marker of Neuroprotection in Methamphetamine-Lesioned Mice Treated Acutely with Estradiol

Abstract: Our laboratories have shown the positive effect of estradiol on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine- and methamphetamine (MA)-induced striatal dopamine (DA) depletion. Most studies on E neuroprotection use chronic administration of the steroid to evaluate its beneficial effect. In the present report, we investigated the neuroprotective potential of 17β-estradiol-3-benzoate (E) under acute conditions when administered 24, 12 or 0.5 h before MA. The effects of E on striatal DA and dihydroxyphenylacetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Such findings highlight an additional characteristic of MA-induced NSDA neurotoxicity as they suggest the potential for a combination of effects exerted by estrogen and testosterone as contributing to the sex differences obtained. In support of this possibility are data which demonstrate that estrogen can act to diminish striatal DA depletions [14, 15,39,40,41,42] while testosterone either has no effect or displays a tendency to increase striatal DA depletions [43, 44] to MA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings highlight an additional characteristic of MA-induced NSDA neurotoxicity as they suggest the potential for a combination of effects exerted by estrogen and testosterone as contributing to the sex differences obtained. In support of this possibility are data which demonstrate that estrogen can act to diminish striatal DA depletions [14, 15,39,40,41,42] while testosterone either has no effect or displays a tendency to increase striatal DA depletions [43, 44] to MA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dissimilarities in gonadal steroid hormones may result in bidirectional effects upon MA-induced neurotoxicity within the NSDA system. This follows from data which show that estrogen can function as a neuroprotectant against MA-induced NSDA neurodegeneration [14, 15,39,40,41,42], while testosterone has no such neuroprotective effects [43], and may exacerbate MA-induced NSDA neurodegeneration [44]. …”
Section: Discussionmentioning
confidence: 99%
“…This gender difference may, in part, be attributable to estrogen since epidemiological studies have demonstrated a beneficial role of estrogens in PD [3, 4]. Laboratory studies have also shown the protective potential of estrogens on brain against methamphetamine (MA) [5,6,7,8,9] and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) [10, 11], two substances that induce damages similar to those encountered in PD [12]. Although these positive effects are well documented, concerns have been raised regarding the clinical use of estrogens.…”
Section: Introductionmentioning
confidence: 99%
“…Included in this assessment were measures of DA concentrations and transporters, as well as preproenkephalin (PPE) expression. Striatal DA concentration is extensively used as a marker of DA neurodegeneration [5,6,7,8,9,10,11]. In the striatum the DA transporter (DAT)-specific binding is on presynaptic DA terminals of substantia nigra DA neurons whereas in the substantia nigra DAT binding is on DA neurons thus giving anatomical information on degeneration of these neurons [23].…”
Section: Introductionmentioning
confidence: 99%
“…Sex steroids have been found to affect neurotransmitters and neurotransmitter receptors of the dopaminergic systems in complex ways, at least in cell and animal studies (Becker 1999, Eaton et al 1999, Andersen et al 2002, Landry et al 2002, Halbreich & Kahn 2003, D'Astous et al 2004. In humans, the potential effects of sex hormone administration on dopaminergic activity have not yet been studied extensively (Lobo et al 1984, Hannan et al 1991, Paoletti et al 2001.…”
Section: Introductionmentioning
confidence: 99%